Annual review of comparative and international education 2013 - Wiseman, Alexander W., 1968-; Anderson, Emily (Bingley, U.K. : Emerald, 2013)
This inaugural volume is a forum for stakeholders and scholars to examine current trends and identify future directions in comparative and international education, using several essays as a context for discussion and analysis. Contributors address the questions and themes discussed in these essays including: the use of new conceptual or methodological frameworks; the role of CIE in teacher education and higher education; the emergence of new area studies, and diversification of the field to include human rights. The volume provides an analytic overview of published work in the field, with discussions of education theory, policy and practice. Chapters in this annual review both highlight the strengths in the field as well as the exciting and up-and-coming developments in theory, method, practice, and research. This annual review will bring together both scholars and stakeholders in the field to highlight those developments of particular relevance to contemporary and future educational reform and school/classroom applications.
Reflections on the field of comparative and international education, and the benefits of an annual review / Alexander W. Wiseman, Emily Anderson -- Introduction to part 2 : comparative education trends and directions / Alexander W. Wiseman, Emily Anderson -- Comparative and international education in Spain : current approaches and directions for future teaching and research / Luis Miguel Lázaro -- Comparative education : a Brazilian perspective / Marta Luz Sisson de Castro -- Mexican perspectives in comparative and international education / Marco Aurelio Navarro, Carlos Ornelas -- Comparative education : inventory and perspectives from an "AFDECE" point of view / Dominique Groux -- Comparative and international education in China : definitions, functions and trends / Wang Yingjie -- Comparative education in the gulf : in search of a foothold / Ali S. Ibrahim -- Introduction to part 3 : conceptual and methodological developments / Alexander W. Wiseman, Emily Anderson -- Comparative education facing the new politics of the otherness : some conceptual developments for the field / Régis Malet -- Shifting the discourse on neo-institutional theory in comparative and international education / Alexander W. Wiseman, Audree Chase-Mayoral -- Introduction to part 4 : research-to-practice / Alexander W. Wiseman, Emily Anderson -- Private sector engagement in education worldwide : conceptual and critical challenges / Francine Menashy -- Introduction to part 5 : area studies and regional developments / Alexander W. Wiseman, Emily Anderson -- Comparative education and the Arabian gulf / Daniel J. Kirk -- Comparative pedagogy in Slavonic south east European countries / Klara Skubic Ermenc ... [et al.] -- Introduction to part 6 : diversification of the field / Alexander W. Wiseman, Emily Anderson -- Cross-cultural approaches to the study of "inclusive" and "special needs" education / Simona DAlessio, Steven Cowan -- Reflections on the annual review and recommendations for institutionalizing reflection in the field / Alexander W. Wiseman, Emily Anderson.
Includes index.
Print version record
Keywords: Education -- Educational Policy & Reform -- General; Education -- Research; Education -- General; Educational strategies & policy; Organization & management of education; Comparative education; International education